The Influence of Competence and Career Development on Employee Performance With Work Motivation as a Mediating Variable in the Back Office Department of Pt. Sumber Alfaria Trijaya Sidoarjo Branch - Arie Ardiansyah Siswanto; Dhani Icsanuddin Nur; Sugeng Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2025)
The purpose of this research is to determine the effect of competence and career development on employee performance with work motivation as a mediation variable. The research method used is descriptive quantitative approach using Smart-PLS software. This study used a sample of 70 respondents from employees in the Department of Sumber Alfaria Trijaya Sidoarjo Branch. The results showed that: 1) competence affects employee performance, 2) Career Development affects employee performance, 3) work motivation can mediate the effect of competence on employee performance 4) work motivation can mediate the effect of career development on employee performance.